Dry friction of microstructured polymer surfaces inspired by snake skin - Baum, Martina J.; Heepe, Lars; Fadeeva, Elena; Gorb, Stanislav N. (Beilstein Journal of Nanotechnology, 2014)
The microstructure investigated in this study was inspired by the anisotropic microornamentation of scales from the ventral body side of the California King Snake (Lampropeltis getula californiae). Frictional properties of snake-inspired microstructured polymer surface (SIMPS) made of epoxy resin were characterised in contact with a smooth glass ball by a microtribometer in two perpendicular directions. The SIMPS exhibited a considerable frictional anisotropy: Frictional coefficients measured along the microstructure were about 33% lower than those measured in the opposite direction. Frictional coefficients were compared to those obtained on other types of surface microstructure: (i) smooth ones, (ii) rough ones, and (iii) ones with periodic groove-like microstructures of different dimensions. The results demonstrate the existence of a common pattern of interaction between two general effects that influence friction: (1) molecular interaction depending on real contact area and (2) the mechanical interlocking of both contacting surfaces. The strongest reduction of the frictional coefficient, compared to the smooth reference surface, was observed at a medium range of surface structure dimensions suggesting a trade-off between these two effects.
Keywords: biomimetics; dry friction; microstructure; polymer; snake skin